The Educational Resources Information Center - Educational Resources Information Center (U.S.); National Library of Education (U.S.) ([Washington, D.C.] : National Library of Education)
National information system designed to provide access to education-related literature. Includes abstracts of documents and journal articles on education research and practice.
Title from home page as viewed on June 21, 2000.
Keywords: Education -- United States -- Computer network resources; Education -- United States -- Electronic information resources